245 GHz SiGe sensor system for gas spectroscopy. Issue 3 (5th February 2015) - Schmalz, Klaus; Wang, Ruoyu; Debski, Wojciech; Gulan, Heiko; Borngräber, Johannes; Neumaier, Philipp; Hübers, Heinz-Wilhelm
Abstract : A 245 GHz sensor system for gas spectroscopy is presented, which includes a SiGe receiver (RX), a SiGe transmitter (TX), and a 0.6 m long gas absorption cell between the TX and RX. The integrated local oscillators of the RX and the TX are controlled by two external phase locked loops (PLLs), whose reference frequencies are swept with constant frequency offset for a low IF of the RX. The RX consists of a differential low noise amplifier (LNA), an integrated 122 GHz local oscillator (LO) with 1/64 divider, a 90° differential hybrid, and active subharmonic mixer. The TX consists of an integrated 122 GHz LO with 1/64 divider, and a frequency doubler. The RX and TX are fabricated in 0.13 µm SiGe BiCMOS with ft/fmax of 300/500 GHz. Using external dielectric lenses for the TX and RX, the absorption spectrum of gaseous methanol has been measured. The reference frequency of the TX-PLL is modulated for frequency-modulation spectroscopy. The performance of the sensor system is demonstrated by measuring the 2f absorption spectrum (second harmonic detection) of gaseous methanol.